Chuck Close prints : Process and collaboration. - D'Amario, Julia; Blanton, Robert; Brown, Kathan; Close, Chuck; Hall, Bill; Hecksher, Karl; Irvine, Alexandra; Lingen, Ruth; Little, Thomas; Shibata, Yasu; Shiff, Richard; Shore, Mae; et al. (Blaffer Gallery, the Art Museum of the University of Houston Princeton University Press, 2003)
Featuring exquisite reproductions of the prints together with essays on Close's career and in-depth interviews with the artist and his master printmakers, Chuck Close Prints highlights the intensely collaborative nature of Close's projects. Close may labor on a single print for as long as two yearss, working out aesthetic problems by tretrieving a centuries-old European method or creating an entirely new technique (such as applying sunscreen to block light). According to Close, "Prints have moved me in my unique work more than anything else has."
For three decades, Chuck Close has challenged the accepted boundaries of the printmaking tradition. This book, published to accompany a retrospective of his prints organized by Blaffer Galllery, the Art Museum of the University of Houston, and traveling to the Metropolitan Museum of Art and several additional museums around the country, is the first comprehensive survey of Close's revolutionary prints.
From the artist's ambitious first mezzotint to his recent pulp-paper multiples, this book chronicles the genius of Chuck Close in the medium in which he has done his most exciting work. Taken together, these prints constitute a remarkable self-portrait of the creative drive, vision, and intellect of one of America's most important living artists.
biog. p. 141-147
Engels
boek
Keywords: Close, Chuck